2004
DOI: 10.5194/angeo-22-1407-2004
|View full text |Cite
|
Sign up to set email alerts
|

All-weather volume imaging of the boundary layer and troposphere using the MU radar

Abstract: Abstract. This paper shows the first volume-imaging radar that can run in any weather, revealing the turbulent threedimensional structure and airflow of convective cells, rain clouds, breaking waves and deep convection as they evolve and move. Precipitation and clear air can be volume-imaged independently. Birds are detected as small high-power echoes moving near horizontal, at different speeds and directions from background wind. The volume-imaging method could be used to create a real-time virtual-reality vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…This result is compatible with the more intermittent and inhomogeneous characteristics of the weakly stable upper troposphere (e.g. Worthington, 2004). Thus, the averaging procedure affects more significantly the quality of the comparisons of the profiles at tropospheric heights.…”
Section: Profilessupporting
confidence: 73%
“…This result is compatible with the more intermittent and inhomogeneous characteristics of the weakly stable upper troposphere (e.g. Worthington, 2004). Thus, the averaging procedure affects more significantly the quality of the comparisons of the profiles at tropospheric heights.…”
Section: Profilessupporting
confidence: 73%
“…Other authors (e.g. Worthington, 2004;Adachi et al, 2005;Ishihara et al, 2006) have reported inhomogeneities between the observations made in different beam pointing directions under convective conditions. Based on the above experiences, it was anticipated that the distribution of full complementary-beam-continuity factor values would be mostly concentrated around zero, but with a small spread at much larger values.…”
Section: Exploitation Of Complementary-beam Informationmentioning
confidence: 99%
“…Fig. 3c of Worthington (2004). Nevertheless, radiosondes show a convective boundary layer to ∼1.3 km AGL in Figs.…”
Section: Introductionmentioning
confidence: 99%
“…The beam transmitted by the entire radar array switches direction every 400 µ s to volume-image the atmosphere, with range resolution 150 m and transmitted beamwidth 3.6 • . Measurement time is 64 beams ×400 µ s inter-pulse-period ×1 incoherent integration ×2 coherent integrations ×128 FFT points=6.55 s. The MU radar mode is identical to 15-16 July 2002in Worthington (2004. Volumeimaging refers only to three-dimensional measurement of atmosphere, not e.g.…”
Section: Introductionmentioning
confidence: 99%